The wheatbelt woodlands of Western Australia - Lessons from the invertebrates - Majer, Jonathan; Recher, H. F.; Lyons, A. (2010)
The majority of our studies of woodland invertebrate have been conducted in the Wandoo (Eucalyptus wandoo and E. capitata) woodland region of Western Australia (see map below). This region, which is immediately to the east of the Jarrah/Marri (E. marginata/Corymbia calophylla) forest, gives way to lower mallee formations, before blending into the Great Western Woodlands, which lie beyond the agricultural clearing line to the east. Due to the adequate rainfall and suitability of the soil for agriculture, this Wandoo/Mallee area is known as the Western Australian wheatbelt, and over 90% of it has been cleared for agricultural production (Environmental Protection Authority 2007).